(untitled) (Research, Society and Development, 2020)
Objective: To review the literature in an integrative way on the peri-implantitis association in patients with pre-existing periodontal disease. Method: The research began to be operationalized from September to November 2020 from a consultation with the Health Sciences Descriptors (DeCS) and the MeSH, namely: peri-implantitis, periodontal disease and risk factors. The inclusion criteria were original articles that addressed the variables defined by the PICO strategy, with a summary and full text accessible in English and published in the period of the last ten years, that fit the guiding question of the study. Systematic reviews and narratives and studies that did not answer the guiding question were excluded from the research. The inclusion and exclusion criteria were established by a consensus reached by all authors, considering the research question and the study objectives, in an attempt to obtain a wide range of results from the search strategy. Results: Through the search strategy used in this review, 09 articles were selected from PubMed and 42 articles from VHL (Virtual Health Library). With the application, the exclusion criteria resulted in 04 articles, which were included in this review. The research included case-control studies, cross-sectional studies and prospective cohort. Conclusion: According to the information obtained in the present study, patients with a diagnosis or history of periodontitis had a higher risk for the occurrence of peri-implantitis, especially those with a history of severe periodontal disease.